PENGARUH BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA (STUDI PADA RUMAH SAKIT MAWADDAH MEDIKA MOJOKERTO) - Muhammad, Bagus Nur; Risanto, Yusuf (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to analyze the influence of organizational culture on job satisfaction in Rumah Sakit Mawaddah Medika Mojokerto. To determine how much influence the independent variable (organizational culture) on the dependent variable ( job satisfaction ) used regression analysis with t test analysis method and f. This study used a sample of 89 RS Mawaddah Employeâ€™s. While the sample using random sampling technique. The results showed that the organizational culture with the variables simultaneously influence on job satisfaction (Y). Partially principle objective (X1), Principle of Intimacy (X3), Principles of Excellence (X5) and the principle of Achievement (X7) a significant effect on job satisfaction (Y), while the principle of consensus (X2), Principle of Integrity (X4) and the principle of Unity ( X6) is not. And the dominant variable is principle objective (X1). Â Â Kata Kunci : Budaya Organisasi, Kepuasan Kerja